Beam Energy Dependence of Hanbury-Brown-Twiss Radii from a Blast-Wave Model - S. Zhang; Y. G. Ma; J. H. Chen; C. Zhong (Advances in High Energy Physics)
The beam energy dependence of correlation lengths (the Hanbury-Brown-Twiss radii) is calculated by using a blast-wave model and the results are comparable with those from RHIC-STAR beam energy scan data as well as the LHC-ALICE measurements. A set of parameters for the blast-wave model as a function of beam energy under study are obtained by fit to the HBT radii at each energy point. The transverse momentum dependence of HBT radii is presented with the extracted parameters for Au+Au collision at sNN = 200 GeV and for Pb+Pb collisions at 2.76 TeV. From our study one can learn that particle emission duration cannot be ignored while calculating the HBT radii with the same parameters. And tuning kinetic freeze-out temperature in a range will result in system lifetime changing in the reverse direction as it is found in RHIC-STAR experiment measurements.